Langerhans cells from women with cervical precancerous lesions become functionally responsive against human papillomavirus after activation with stabilized Poly-I:C - Da Silva, Diane M (Clinical immunology (Orlando, Fla.), 2015)
Copyright © 2015 Elsevier Inc. All rights reserved.